Applying Blockchain Technology to Security-Related Aspects of Electronic Healthcare Record Infrastructure - Adlam, Ryno; Haskins, Bertram (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
The centralised architecture employed by electronic health records (EHRs) may constitute a single point of failure. From the perspective of availability, an alternative cloud-based EHR infrastructure is effective and efficient. However, this increased availability has created challenges related to the security and privacy of patients’ medical records. The sensitive nature of EHRs attracts the attention of cyber-criminals. There has been a rise in the number of data breaches related to EHRs. The infrastructure used by EHRs does not assure the privacy and security of patients’ medical records. Features of blockchain platforms, such as decentralisation, immutability, auditability, and transparency, may provide a viable means of augmenting or improving services related to the security of EHRs. This study presents a series of experimental data flow configurations to test the application of blockchain technology to aspects of EHRs. The insights gained from these experiments are founded on a theoretical base to provide recommendations for applying blockchain technology to services related to the security of EHR infrastructure. These recommendations may be employed by developers when redesigning existing EHR systems or deploying new EHR systems.
Keywords: healthcare, electronic health records (EHRs), blockchain, information security